The reliability of Cameriere's method in Turkish children: A preliminary report. (April 2015) - Gulsahi, A.; Tirali, R. Ebru; Cehreli, S. Burcak; De Luca, S.; Ferrante, L.; Cameriere, R.
Highlights: A sample of 573 digital panoramic radiographs of healthy Turkish children, aged between 8 and 15 years, was studied. Radiographs of the left permanent developing mandibular teeth, were evaluated. Cameriere's method is more accurate for girls than for boys in the tested population. Abstract: Dental age estimation in children is an important issue both legally and medically. Currently, however, there is a lack of contemporary dental age estimation standards for a Turkish population. This study assessed the accuracy of Cameriere's method by examining the panoramic radiographs of 573 healthy Turkish children between the ages of 8 and 15 years. Radiographs of the left permanent developing mandibular teeth, except wisdom teeth, were evaluated. All subjects were divided into 7 groups according to their chronological age. The Intra-class Correlation Coefficient was used to determine the intra- and inter-observer agreement error. A comparison of the distributions of estimation errors among age groups was performed using the Nemenyi test. There were no significant differences between inter-observer ( p  = 0.352), and intra-observer readings after 2 weeks ( p  = 0.275 and p  = 0.273, respectively). The dental age was underestimated when using Cameriere's method with a mean difference of −0.35 years (−0.24 years for girls and −0.47 years for boys). The median values of the differences between dental and chronological age were −0.44 years in boys (range: −3.70, 4.06) and −0.21 years in girls (range: −2.74, 3.29). In addition, the differences between dental and chronological ages in the different age groups decreased with increasing chronological age. Results from the Nemenyi test implied that Cameriere's method is more accurate for girls than for boys in this cohort of a Turkish population.